International experiments with different models of allocating funds to facilitate integrated care: a scoping review protocol. Issue 11 (15th November 2018) - Khayatzadeh-Mahani, Akram; Nolte, Ellen; Sutherland, Jason; Forest, Pierre-Gerlier
Abstract : Introduction: Integrated care is viewed widely as a potential solution to some of the major challenges faced by health and social care systems, such as those posed by service duplication, fragmentation and poor care coordination, and associated impacts on the quality and cost of services. Fragmented models of allocating funds to and across sectors, programmes and providers are frequently cited as a major barrier to integration and countries have experimented with different models of allocating funds to enhance care coordination among service providers and to reduce ineffective care and avoid costly adverse events. This scoping review aims to assess published international experiences of different models of allocating funds to facilitate integration and the evidence on their impacts. Methods and analysis: We will adopt a scoping review methodology due to the potentially vast and multidisciplinary nature of the literature on different models of allocating funds in health and social care systems, as well as the scarcity of existing knowledge syntheses. The framework developed by Arksey and O'Malley will be followed that entails six steps: (1) identifying the research question(s), (2) searching for relevant studies, (3) selecting studies, (4) charting the data, (5) collating, summarising and reporting the results and (6) and conducting consultation exercises. These steps will be conducted iteratively and reflexively, making adjustments and repetitions when appropriate to make sure the literature has been covered as comprehensively as possible. To ensure comprehensiveness of our literature review, we also search a wide range of sources. Ethics and dissemination: An integrated knowledge translation strategy will be pursued by engaging our knowledge users through all stages of the review. We will organise two workshops or policy roundtables/policy dialogues in Alberta and British Columbia with participation of diverse knowledge users to discuss and interpret the findings of our review and to draw out policy opportunities and lessons that can be applied to the context of these two provinces.